2016
DOI: 10.1002/app.43460
|View full text |Cite
|
Sign up to set email alerts
|

Poly(lactic acid) plasticized by biodegradable glyceryl lactate

Abstract: The esterification of glycerol with lactic acid was carried out to synthesize glyceryl lactate, which was used as a as a plasticizer with different contents and blended with poly(lactic acid) (PLA) to get a completely biodegradable material with potential applications because of its biodegradability. The structural, morphological, thermal, and mechanical properties of the plasticized PLA were studied to evaluate the plasticizing effects. The results show that the PLA plasticized with glyceryl lactate had a low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 39 publications
1
12
0
Order By: Relevance
“…At higher temperature, the molecular interactions between PLA chains and TBR were weakened which allowed TBR to migrate easier. 21 Moreover, the migration of TBR also increased as its contents increased at the same times for all temperatures studied. In comparison, the amount of plasticizer migration observed in the current paper was lower than that observed in other plasticized PLA and PLA/PHA blends such as glyceryl lactate 21 and ester of citric acid.…”
Section: Migration Of Tbrmentioning
confidence: 84%
“…At higher temperature, the molecular interactions between PLA chains and TBR were weakened which allowed TBR to migrate easier. 21 Moreover, the migration of TBR also increased as its contents increased at the same times for all temperatures studied. In comparison, the amount of plasticizer migration observed in the current paper was lower than that observed in other plasticized PLA and PLA/PHA blends such as glyceryl lactate 21 and ester of citric acid.…”
Section: Migration Of Tbrmentioning
confidence: 84%
“…The presence of plasticizers in the PLA-based films is a usual method that is often used to enhance the flexibility, extensibility, and processability of PLA by increasing the mobility of polymer chains (Darie-Niţă et al, 2016;Fadl & Madkour, 2019;. However, due to their high mobility and low molecular weight, plasticizers can migrate to the matrix surface and contaminate materials in direct contact with plasticized PLA (Hassouna et al, 2012;Ljungberg & Wesslen, 2002;Yuan et al, 2016). Therefore, the selection of appropriate plasticizers with low volatility and moderate molecular weight in proper amounts is essential for food packaging application (Hassouna et al, 2011;Ljungberg & Wesslen, 2003;Murariu et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Plasticizing agents such as oligomeric lactic acid (OLA) (Burgos et al, 2013;Luzi et al, 2019), glycerol (Risyon et al, 2016), polyethylene glycol (PEG) (Arrieta et al, 2014;Courgneau et al, 2011), tributyl citrate (TBC) (Ljungberg & Wesslen, 2003;Yang et al, 2018), acetyltributyl citrate (ATBC) Arrieta et al, 2014), triethyl citrate (TEC) (Arrieta, de Dicastillo, et al, 2018), acetyltriethyl citrate (ATEC) (Shirai et al, 2013), and triacetin (TA) (Fadl & Madkour, 2019;Grigale-Soročina et al, 2010; are often mentioned as effective plasticizers for PLA plasticization. It has been reported that plasticizers have effectively increased elongation of PLA by facilitating its chains mobility and reducing interaction forces (hydrogen bonds) in the polymer matrix (Darie-Niţă et al, 2016;Yuan et al, 2016). However, as the concentration of plasticizer increases, the water permeability of the PLA films increases due to the high physisorption affinity of water molecules to PLA.…”
Section: Introductionmentioning
confidence: 99%
“…To overcome these limitations and extend the possibility of more widespread usage, the flexibility and toughness of PLA can be improved by modifying its brittleness. The problem of enhancing the ductile properties of PLA in impact toughness and elongation at break while maintaining its biodegradability is approached in 3 main ways: physical blending with other flexible polymers, plasticization, and copolymerization with other monomers . Polylactide copolymerization is effective, but the technique is complicated, the cost relatively high, and industrial scale‐up difficult .…”
Section: Introductionmentioning
confidence: 99%